2011
DOI: 10.1007/s11426-010-4180-z
|View full text |Cite
|
Sign up to set email alerts
|

SmI2-promoted imino-Reformatsky reaction for facile synthesis of enantioenriched β-amino acid esters

Abstract: A facile and efficient method for the stereoselective synthesis of -amino acid esters via SmI 2 -promoted imino-Reformatsky reaction is described. Asymmetric addition of tert-butyl bromoacetate to N-tert-butanesulfinyl aldimines afforded -amino acid esters in moderate to high yields with excellent diastereoselectivities. The synthetic utilities of the tert-butyl -amino acid esters were expanded by the preparation of -lactams and 3-aminoindan-1-ones derivatives.-amino acid ester, samarium diiodide, N-tert-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The imine 85 was then reacted with tertbutyl bromoacetate/SmI 2 to give 86. 57,58 Treatment of 86 under acidic conditions provided the amino acid 87, which was The synthesis of sulfonamides 28−33 is described in Scheme 10. The synthesis of these analogs starts from the chiral ketone 93 which was converted to hydroxylamine derivative 106.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…The imine 85 was then reacted with tertbutyl bromoacetate/SmI 2 to give 86. 57,58 Treatment of 86 under acidic conditions provided the amino acid 87, which was The synthesis of sulfonamides 28−33 is described in Scheme 10. The synthesis of these analogs starts from the chiral ketone 93 which was converted to hydroxylamine derivative 106.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…The organic extracts were collected and washed with brine solution, dried (Na 2 SO 4 ) and solvent was removed to provide crude 56 as a brownish liquid (4.0 g, 75% crude yield). 1 Step 2: tert-Butyl (6-Bromo-2,3-dihydro-1H-inden-1-yl)(methyl)carbamate (57). To a solution of 56 (4 g, 17.7 mmol) in DCM (500 mL) at 0 °C were added (Boc) 2 O (7.72 g, 35.39 mmol), TEA (3.58g, 35.39 mmol), and DMAP (50 mg).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…One year later, M.-H. Xu et al reported also an asymmetric imino-Reformatsky reaction using SmI 2 . 22 They optimized the reaction conditions between different arylsubstituted N-tertbutylsulfinyl aldimines 21 and the tert-butyl bromo ester 22.…”
Section: Synthesis Of Enantiopure Acyclic Moietiesmentioning
confidence: 99%